33.5k views
25 votes
Please help I need by Tomorrow!

Please help I need by Tomorrow!-example-1
User Compulim
by
4.9k points

1 Answer

5 votes

Answer:


f(a) = 5a + 1


f(a + h) = 5a + 5h +1


(f(a + h) - f(a))/(h) =5

Explanation:

Given


f(x) = 5x + 1

Solving (a): f(a)

Substitute a for x in
f(x) = 5x + 1


f(a) = 5a + 1

Solving (b): f(a + h)

Substitute a + h for x in
f(x) = 5x + 1


f(a + h) = 5(a + h) +1

Open bracket


f(a + h) = 5a + 5h +1

Solving (c):
(f(a + h) - f(a))/(h)

In (a):


f(a) = 5a + 1

In (b):


f(a + h) = 5a + 5h +1

So:


(f(a + h) - f(a))/(h) =(5a+5h+1 - (5a+1))/(h)

Open bracket


(f(a + h) - f(a))/(h) =(5a+5h+1 - 5a-1)/(h)

Collect Like Terms


(f(a + h) - f(a))/(h) =(5a- 5a+5h+1 -1)/(h)


(f(a + h) - f(a))/(h) =(5h)/(h)


(f(a + h) - f(a))/(h) =5

User Flowstoneknight
by
4.6k points